Liquidity, Solvability, Profitability, Size of Company Impact on Stock Prices In Health Service Companies - Hospitals With Dividend Policy As An Intervening Variable Listed On Indonesia Stock Exchange 2018 - 2022 Period - Faturohman Faturohman; Riyanti Riyanti; Luqman Hakim (Journal Research of Social Science, Economics, and Management, 2024)
This study aims to evaluate the impact of liquidity ratio, solvency, profitability, and company size on stock prices, with dividend policy as an intervening variable. The study population includes all healthcare companies listed on the Indonesia Stock Exchange during the period 2018 to 2022, totaling 28 issuers. The research sample was selected using the purposive sampling method, resulting in 6 companies as a sample, with 5 years of research, so that there were 30 observations. The analysis technique used is path analysis, which is carried out with the help of SPSS software version 25. Hypothesis testing is carried out by multiple linear regression. The findings of the study indicate that CR and firm size have a direct effect on dividend policy. In addition, the DER and the size of the company have a direct influence on the stock price. The indirect influence (intervening) was analyzed using the Sobel test, which showed that liquidity (CR), profitability (ROE), and firm size had a significant effect on stock prices through dividend policy (DPR), but were unable to mediate the relationship between solvency (DER) and stock prices.